Kewirausahaan Berbasis Bokashi: Tekhnik Pengolahan, Pemasaran Digital dan Pembukuan Sederhana bagi Alumni - Sabat, Diana; Deno Ratu, Maria Rosdiana; Ni Made Paramita Setyani; Bastari Sabtu; Jalaludin; Petrus Kune; Tenang; Hendrikus Umbu Padu (Bakti Cendana, 2025)
The management of organic waste from the livestock sector is a significant challenge in achieving sustainable agricultural practices. The problem of poorly managed livestock waste can cause environmental pollution and contribute to greenhouse gas emissions. Therefore, the Community Service (PkM) activity was carried out at the Faculty of Animal Husbandry, Marine and Fisheries, Nusa Cendana University, aiming to improve the understanding and skills of alumni and final year students of the Animal Husbandry Study Program in processing waste into quality bokashi fertiliser. This activity took place from 17 April to 14 May 2024, involving 23 participants, including lecturers and partners. The methods applied included distribution of extension materials, socialisation, bokashi processing training, as well as financial management and digital marketing training. The evaluation results showed a significant increase in partners' understanding of various aspects. The biggest improvement was recorded in the aspect of simple bookkeeping, with 65% of respondents feeling more able to record transactions systematically using spreadsheet software. In addition, understanding of bokashi fertiliser processing technology increased by 35%, packaging by 38%, and digital marketing by 50%. Overall, this activity succeeded in increasing the skills (soft skills and hard skills) of partners by 40%